Differences in levels of bone morphogenetic protein-2 in periodontitis patients with and without type 2 diabetes mellitus - Pritama, Muhammad Fauzi Adityawan; Syaify, Ahmad; Suryono, Suryono (Majalah Kedokteran Gigi Indonesia, 2023)
Periodontitis is characterized by gingival bleeding, periodontal pocket formation, damage to the connective tissue attachment, and alveolar bone resorption. One of the risk factors that can increase the occurrence of periodontitis is diabetes mellitus (DM). In Indonesia, the incidence and prevalence of periodontitis are higher in patients with type 2 DM. In the present study, BMP-2 expression in periodontitis patients with and without type 2 DM was evaluated. We performed a descriptive analytical cross-sectional study in 40 respondents with stages II-III grades B-C chronic periodontitis. They were divided into a chronic periodontitis group with type 2 DM and a chronic periodontitis group without DM. Crevicular fluid of the gingival sulcus of the central maxillary anterior teeth from each respondent was taken using paper points for 5 minutes and placed in an Eppendorf tube. Each tube was labelled according to its group. All of the samples were examined by BMP-2 ELISA kit and measured by BioRad microplate reader with a wavelength of 450 nm. Data were analysed using SPSS 16.0 program. The independent sample t-test was used to compare the BMP-2 among two groups. The results of the study revealed the BMP-2 level in periodontitis patients with type 2 DM was 63.1 pg/ml, while in periodontitis patients without DM was 66.8 pg/ml. BMP-2 levels in periodontitis patients with type 2 DM were significantly lower than those in periodontitis patients without DM (p < 0.05).